Kontribusi Pajak Provinsi Dan Pajak Kabupaten/Kota Terhadap Penerimaan Pajak Daerah (Studi Kasus: Provinsi DKI Jakarta 2017-2022) - Lenny Panggabean (Universitas Katolik Soegijapranata, Semarang, 2022)
Local taxes is original and the largest revenue in the budget and revenue; excluding retribution, segregated asset management results, and other legal original income. The aim of this research was to find out how much the contribution of the types of local taxes to the total local tax revenue during 2017-2022 fiscal year. The studied objects were 13 types of local taxes of the DKI Jakarta Provincial Government. The secondary data were used by this quantitative and descriptive research methods. The research problems included how much the contribution of the local taxes in the provincial tax revenues, how much the contributions of local taxes in district/city tax revenues and how much contributions of provincial taxes and district/city taxes in total local tax revenues managed by Regional Revenue Body (Badan Pendapatan Daerah) of DKI Jakarta. The conclusion for the first problem was the Motor Vehicle Tax (PKB) as the contributor in the provincial tax. The second, it was found that local taxes that had the highest contribution to provincial taxes were PBB-P2 and BPHTB, while for the third problem was found that district/city taxes contributed a higher contribution than provincial taxes to total local tax revenues.